Addressing Integration Challenges of Interdisciplinary Research in Social-Ecological Systems. Issue 3 (3rd March 2020) - Pricope, Narcisa Gabriela; Cassidy, Lin; Gaughan, Andrea Elizabeth; Salerno, Jonathan David; Stevens, Forrest Robert; Hartter, Joel; Drake, Michael; Mupeta-Muyamwa, Patricia
Abstract: Conducting research on coupled social-ecological systems (SESs) presents inherent challenges, such as coordination across disparate disciplines or integrating across multiple scales and levels of governance. To overcome these common challenges, we propose that structuring the research design itself according to SES principles provides for integrative execution of SES science. First, starting with pilot work, human and natural science researchers should work as a team to identify and access multi-level entry points (i.e. points of direct engagement) within the system, relative to the spatiotemporal scales under investigation. Second, teams should implement an adaptive process that begins with the proposed research design and uses shared experiences from pilot work to refine protocols prior to subsequent data collection. We provide examples of multi-level and multi-scale entry points, and show that adaptive management of research design through coordinated iteration allows for better research integration and applicable outcomes.